A low-temperature ductile shear zone: The gypsum-dominated western extension of the brittle Fella-Sava Fault, Southern Alps - Bartel, Esther Maria; Neubauer, Franz; Heberer, Bianca; Genser, Johann (Journal of structural geology, 2014)
Based on structural and fabric analyses at variable scales we investigate the evaporitic gypsum-dominated Comeglians-Paularo shear zone in the Southern Alps (Friuli). It represents the lateral western termination of the brittle Fella-Sava Fault. Missing dehydration products of gypsum and the lack of annealing indicate temperatures below 100 °C during development of the shear zone. Despite of such low temperatures the shear zone clearly exhibits mylonitic flow, thus evidencing laterally coeval activity of brittle and viscous deformation. The dominant structures within the gypsum rocks of the Lower Bellerophon Formation are a steeply to gently S-dipping foliation, a subhorizontal stretching lineation and pure shear-dominated porphyroclast systems. A subordinate simple shear component with dextral displacement is indicated by scattered σ-clasts. Both meso- and microscale structures are characteristic of a subsimple shear type of deformation with components of both coaxial and non-coaxial strain. Shortening in a transpressive regime was accommodated by right-lateral displacement and internal pure shear deformation within the Comeglians-Paularo shear zone. The shear zone shows evidence for a combination of two stretching faults, where stretching occurred in the rheologically weaker gypsum member and brittle behavior in enveloping lithologies. [Display omitted] •The Comeglians-Paularo shear zone is the western extension of the Fella-Sava Fault.•Steeply dipping gypsum determines propagation and termination of the shear zone.•Mylonitic deformation of gypsum in the shear zone occurred at temperatures <100 °C.•The shear zone impedes fluid flow and possibly earthquake propagation.